(untitled) (Research, Society and Development, 2020)
Brazil is a tropical country and its east coast faces the Atlantic Ocean, where there is a set of beaches with a lush landscape. Both the Brazilian population and foreign tourists have as culture, the search for beaches for their leisure throughout the year. Tombo beach, the main object of this study related to primary contact bathing, is located in Guarujá - Baixada Santista /SP - Brazil. The aim of this study is to understand the relationship between the socio-environmental and socioeconomic conditions of Tombo beach and the annual bathing beach indexes, over the period 2010-2018. Secondary data from the São Paulo State Environmental Company, CETESB, which monitors the healthiness of the São Paulo beaches, were used, and maps were made on environmental health including sanitary sewage, urban solid waste and urban drainage, based on informations from the Brazilian Institute of Geography and Statistics. The results show that the environmental management practiced in the study area is of high health, which translates into proper conditions for bathing, over the years analyzed.